DYNAMIQUE DÉMOGRAPHIQUE ET ÉCONOMIQUE, FACTEURS DÉTERMINANTS DE LA CROISSANCE SPATIALE DES VILLES DU DÉPARTEMENT DE SOUBRÉ (CÔTE D’IVOIRE) - Daniel, Kouadio Yao; Jérôme, Aloko-N’guessan (European Scientific Journal, ESJ, 2015)
The department of Soubré was struck by a sub settlement observed over a long period in the history of Côte d’Ivoire. The immense natural potential, the decline of the "cocoa Loop" in the regions of Eastern and Central East and the start of the South West Development Project (ARSO) initiated by the State ended up upsetting the departmental space. Indeed, the department of Soubré has become a reception area where the plantation economy takes a boom since the 1975/1980 year. The study shows that immigration that was particularly intensified in the department of Soubré is the origin of socio-demographic change and urban socio-economic department. However, it retains the light of the above that the farmers through their major agricultural income from the plantation economy have a real grip on the urban extension.